The Activation Pattern of Drug-Reacting T Cells Has an Impact on the Clinical Picture of Hypersensitivity Reactions - Wuillemin, Natascha; Ballmer-Weber, Barbara; Schlapbach, Christoph; Jörg, Lukas; Yerly, Daniel (Frontiers in Allergy, 2022)
Rationale β-lactam antibiotics cause drug hypersensitivity reactions (DHR) with various clinical pictures from minor affections like maculopapular exanthema (MPE) and urticaria to severe cutaneous adverse reactions and anaphylaxis. Currently, two different reactivity patterns have been shown to initiate an immune reaction by activating T cells—the hapten concept and the pharmacological interaction with immune receptor (p–i) concept. Objectives In this study, the relationship between the reactivity pattern of drug-reacting T cells of drug allergic patients and their clinical picture has been investigated. Findings Drug-reacting T-cell clones (TCCs) were isolated from patients hypersensitive to β-lactams. Analysis of their reactivity pattern revealed an exclusive use of the hapten mechanism for patients with immediate reactions and for patients of MPE. In patients suffering from drug reactions with eosinophils and systemic symptoms, a severe DHR, analysis of isolated drug-reacting TCC identified the p–i concept as the unique mechanism for T-cell activation. Conclusions The results show a shift from hapten pattern in mild allergic reactions to p–i pattern in severe life-threatening allergic reactions. They strongly argue against the current preclinical risk evaluation of new drugs based on the ability to form haptens.